Antibiotic use and risk of autism spectrum disorder and attention-deficit/hyperactivity disorder: a population-based cohort study - Kai-Lin Yang; Ting-An Yen; Fang-Ju Lin; Chien-Ning Hsu; Chi-Chuan Wang (BMC, 2024)
Abstract Background The gut microbiota is believed to influence neurodevelopment through the gut-brain axis, but prior studies have shown inconsistent results regarding early childhood antibiotic exposure and subsequent risk of autism spectrum disorder (ASD) and attention-deficit/hyperactivity disorder (ADHD). The purpose of this study was to evaluate the hypothesis that exposure to antibacterial agents in the first 2 years of life increases the risk of ASD and/or ADHD. Methods This was a retrospective cohort study using 2003-2019 data from the National Health Insurance Research Database in Taiwan. Livebirths born between 2004 and 2016 were identified and separated into singleton, full sibling, and exposure-discordant sibling pair cohorts. The exposure group included children who filled at least one prescription for antibacterial agents between 0 and 2 years old in outpatient settings. The outcome, ASD and/or ADHD, was defined by at least one inpatient or outpatient diagnosis. The maximum follow-up age was 15 years in this study. Potential neonatal, maternal and paternal confounders were adjusted for. Cox proportional hazards models were used to estimate the relative event risk. Results The final sample contained 946,581 children in the singleton cohort, 1,142,693 children in the full sibling cohort, and 352,612 children in the exposure-discordant sibling pair cohort. Antibiotic exposure marginally increased the risk of ASD and/or ADHD in the singleton cohort (adjusted hazard ratio [aHR]: 1.06, 95% confidence interval [CI]: 1.04-1.07) and in the full sibling cohort (aHR: 1.03, 95% CI: 1.01-1.04). A slight decrease in the risk of ASD and/or ADHD was observed in the exposure-discordant sibling pair cohort (aHR: 0.92, 95% CI: 0.90-0.94). Conclusions The results suggest that early life antibiotic exposure has minimal impact on the risk of ASD and/or ADHD. Given that the estimated effects are marginal and close to null, concerns about ASD and/or ADHD risk increase should not postpone or deter timely and reasonable antibiotic use.